Hubungan Status Gizi, Umur, Jenis Kelamin dengan Derajat Infeksi Dengue pada Anak di RSUD Abdul Wahab Sjahranie Samarinda: Relationship between Nutritional Status, Age, Gender and Degree of Dengue Infection in Children at Abdul Wahab Sjahranie Hospital Samarinda - Putri Lintang Kharisma; Annisa Muhyi; Eva Rachmi (Jurnal Sains dan Kesehatan, 2021)
Dengue virus infection can manifest from mild to severe, which are undifferentiated fever, dengue hemorrhagic fever (DD), dengue hemorrhagic fever (DHF), and dengue shock syndrome (DSS), respectively. Mild and severe dengue infection is difficult to distinguish early in the course of the disease, and the clinical course is also difficult to "predict". Therefore, indicators were needed to predict the degree of dengue virus infection, thus appropriate treatment can be given. The study was aimed to determine the association of nutritional status, age, and sex with the degree of dengue infection in children. This study was an analytic observational study with a cross-sectional design. The samples were pediatric patients (0-18 years), who have been diagnosed with dengue virus infection and were hospitalized at the Abdul Wahab Sjahranie Hospital Samarinda in 2019. Purposive sampling technique was used to appointed 88 patients. The data obtained from the medical records. The bivariate association was statistically analyzed with chi-square test. The result showed a significant association between sex (p = 0.041) with the degree of dengue infection in children. Meanwhile nutritional status (p = 0.127) and age (p = 0.077) had no significant association with the degree of dengue infection in children. In conclusion, sex might serve as a predictor of the degree of dengue infection in children, in which male is more susceptible to worse manifestations.